MODELING OF INNOVATIVE ACTIVITIES AT AN ENTERPRISE IN THE CONDITIONS OF CORPORATE CULTURE - Anatolyevna Blokhina, Olga; Nikolaevna Zamega, Emma; Aleksandrovich Biryukov, Vladimir; Viktorovna Ukhina, Tatiana; Viacheslavovna Stakhova, Liudmila (Revista Inclusiones, 2020)
The article is devoted to the elaboration of approaches to modeling of innovative activities at an enterprise in the conditions of corporate culture. It has been established that it is necessary to continue further re-search related to the development of management parameters and to develop a system designed to fix innovative processes. It has been proved that in practice, there can be a symbiosis of two or three models as part of the measures taken to form and develop sub-cultures of the corporate culture at an enterprise. Studies have shown that once a model of innovative development is chosen it is essential to focus on how to bring it to fruition. Among possible ways, one can highlight reactive, active, and gradual, which are determined depending on the specified goals and objectives, as well as timeframe indicated for transformation. It has been established that among methods aimed to form and manage innovation and transformation, it is possible to single out the spontaneous method carried out by independently the executive, only by experts and consult-ants on their own, and by the executive when services are provided by experts and consultants.